Exogenous and Endogenous Growth Models: a Critical Review - Themba G. Chirwa; Nicholas M. Odhiambo (Comparative Economic Research. Central and Eastern Europe, 2018)
The main divisions of the theoretical economic growth literature that we study today include exogenous and endogenous growth models that have transitioned through a number of notions and criticisms. Proponents of exogenous growth models argue that technological progress is the key determinant of long-run economic growth as well as international productivity differences. Within the endogenous growth models, there are two notions that are propagated. The first postulates that capital used for innovative purposes can exhibit increasing returns to scale and thus account for the international productivity differences we observe today. The key determinants include knowledge, human capital, and research and development. The second argues that factors that affect the efficiency of capital, and hence cause capital flight, can also explain international productivity differences. These factors that affect the efficiency of capital include government spending, inflation, real exchange rates, and real interest rates. Our study results reveal that there is still no agreement on the dominant theoretical economic growth model amongst economists that can fully account for international productivity differences. We conclude that the future of theoretical economic growth is far from over and more work needs to be done to develop more practical structural economic growth models.
Keywords: B22; E13; N10; O40; 330; economic growth; exogenous growth models; endogenous growth models